Estimation of Seepage Zone at Bajulmati Dam, Banyuwangi Regency Based on Litology Analysis Using Magnetic Data - Hanna Azizah Rahmah; Adi Susilo; Arief Rachmansyah (Natural B, Journal of Health and Environmental Sciences, 2015)
A research regarding seeping in Bajulmati Dam of Banyuwangi Regency based on lithology analysis by geomagnetic data has been done to discover the location of zone with seeping potential. This research is done by analyzing lithology from magnetic data (primary data) that was acquired from the field that covers the area of Bajulmati Dam. The research began with the acquisition of magnetic data using PPM (proton procession Magnetometer). Acquired data is then corrected by diurnal and IGRF correction, reduction in to even surface, upward continuation as well as reduction to the pole. Local anomaly contour is acquired with the value ranging from -1000 nT up to 700 nT at loop 1 and ranging from -2800 nT up to 1600 nT at loop 2. Based on the result of data processing by magnetic method, the subsurface layers beneath the said dam consist of the layer of clay (tuff), sandstone, gravel, and volcanic lava. By analyzing the mentioned results, some cracks are located in AA’ line with the measurement point of 20 m and 90 m, and in the 120 m and 160 m, 80 m and 100 m measurement point of BB’, and CC’ line respectively. Those cracks can be expected to cause seepage in Bajulmati Dam.